Optimizing shape uniformity and increasing structure heights of deep reactive ion etched silicon x-ray lenses. (2nd November 2015) - Stöhr, Frederik; Wright, Jonathan; Simons, Hugh; Michael-Lindhard, Jonas; Hübner, Jörg; Jensen, Flemming; Hansen, Ole; Poulsen, Henning Friis
Abstract: Line-focusing compound silicon x-ray lenses with structure heights exceeding 300 μ m were fabricated using deep reactive ion etching. To ensure profile uniformity over the full height, a new strategy was developed in which the perimeter of the structures was defined by trenches of constant width. The remaining sacrificial material inside the lens cavities was removed by etching through the silicon wafer. Since the wafers become fragile after through-etching, they were then adhesively bonded to a carrier wafer. Individual chips were separated using laser micro machining and the 3D shape of fabricated lenses was thoroughly characterized by a variety of means. Optical testing using synchrotron radiation with a photon energy of 56 keV yielded a 300 μ m wide beam with a waist of 980 nm (full width at half maximum) at a focal length of 1.3 m. Optical aberrations are discussed in the context of the shape analysis, where a slight bowing of the lens sidewalls and an insufficiently uniform apex region are identified as resolution-limiting factors. Despite these, the proposed fabrication route proved a viable approach for producing x-ray lenses with large structure heights and provides the means to improve the resolution and capabilities of modern x-ray techniques such as x-ray microscopy and 3D x-ray diffraction.